Equilibria of the triglycerides + faee + ethanol system and extraction of two immiscible liquid - Nur Athirah, Mohamad Khalil (2015)
The goal of this project is to construct McCabe Thiele chart and ternary diagram for ethyl oleate and triolein under various alcohol compositions. Low grade oils are practically used as a biodiesel feedstock to overcome the high costs of biodiesel production. However, existing processes involved with extra cost of the feedstock pretreatment. This study is to provide extraction characteristic for a separating reactor of biodiesel synthesis for pure raw material before using the low grade feedstock as a benchmark. Liquid-liquid extraction (LLE) is the mechanism used as the alternative method to improve the reactivity of immobilized enzymatic process. In this study, standard sample ethyl oleate and triolein were prepared to plot the calibration curve. Calibration curve was needed to determine the concentration of all components in the system. To prepare the sample, ethyl oleate was mixed with n-heptane with different concentration in 1 ml vial. The same procedure was repeated for triolein sample preparation. Then, the compositions of ethyl oleate and triolein were determined from gas chromatography. The data from GC analysis were used to plot the calibration curve. The work was continued with the preparation of fatty acid ethyl ester (FAEE) through the transesterification reaction of vegetable oils with ethanol by using potassium hydroxide (KOH) and was mixed in conical flasks with triglycerides from palm oil and ethanol. In equilibrium analysis study, two liquid phases clearly separated. One phase is enriched triglycerides at the bottom and enriched ethanol at the top of the layer. After the equilibrium was achieved, a sample was taken from both phases for concentration measurements by using gas chromatography. The GC analysis was carried and the data needed was tabulated in order to determine the peak area and retention time to plot the calibration curve. Next, the concentrations of all samples were determined from the calibration curve to construct McCabe-Thiele charts. From this graph, the composition of triglycerides and FAEE were determined to identify whether extraction process is possible or not and to determine the composition of FAEE and triglycerides whether it rich in solvent phase or solution phase. By referred to the trend of McCabe-Thiele chart for FAEE and triglycerides, the extraction was not possible and stripping would occur in this process since the solvent ratio used is not high enough to achieve effective removal of FAEE from the solution using solvent extraction. In other hand, McCabe-Thiele chart for triglycerides shows addition of FAEE shifted the equilibrium towards the operating line. This may imply that FAEE helps increase concentration of triglycerides in ethanol. For ternary diagram, the result was confirmed that the biodiesel has greater solubility in the triglycerides-enriched phase at constant temperature. From the McCabe-Thiele charts, it was concluded that volume ratio for the solvent must be greater than 1:1 in order to ensure the extraction process can be attained and the increment of FAEE concentration was reduced the solubility of solute (triglycerides) in the solution. Lastly, from the ternary diagram, the compositions that create two immiscible liquid system was successfully obtained and the result shows that biodiesel has greater solubility in the triglycerides-enriched phase in the system containing ethanol at constant temperature.